Brain Activation Follows Adding-Type Integration Laws: Brain and Rating Responses in an Integration Task with pairs of Emotional Faces - Pereira, Telmo (2016)
This study was designed to investigate the relation between rating responses and the patterns of cortical activation in an integration task using pairs of emotional faces. Participants judged on a graphic rating scale the overall affective intensity conveyed by two emotional faces, each presented to one of the two hemispheres via a Divided Visual Field technique (DVF). While they performed the task, EEG was recorded from 6 scalp locations. Three discrete emotions were considered (Joy, Fear, and Anger) and varied across three levels of expression intensity. Some face pairs portrayed the same emotion (same-emotion pairs), others two different emotions (distinct-emotions pairs). The patterns of integration of the two sources of information were examined both at the level of the ratings and of the brain response (event-related-#-desynchronization: ERD) recorded at each EEG lead. Adding-type rules were found for the ratings of both same-emotion and different-emotions pairs. Addingtype integration was also commonly found when #-ERD was taken as a response. Outcomes are discussed with a link to the lateralization of emotional processing and the relations between the observable R (e.g., ratings) and possible implementational aspects of the implicit R posited by Information Integration Theory (IIT).